Revisão do gênero Polyrhaphis Audinet-Serville (Coleoptera, Cerambycidae, Lamiinae) - Santos-Silva, Antonio; Martins, Ubirajara R; Tavakilian, Gérard L (Papéis Avulsos de Zoologia, 2010)
Polyraphis Audinet-Serville, 1835, a genus belonging to the Lamiinae, and distributed between Mexico and South America, excluding Chile and under latitude 35°S, is reviewed. Three new species are described: P. baloupae, from French Guiana; P. lanei, from Brazil (Amazonas and Pará); P. peruana, from Peru. Two species are synonymyzed: P. testacea Lane, 1965 (= P. gracilis Bates, 1862) and P. paraensis [= P. papulosa (Olivier, 1795)]. Neotype to P. papulosa is designated. The authorship of P. horrida [= P. spinosa (Drury, 1773)] is commented. Cerambyx armatus Voet (1778?) is considered an invalid name and Lamia armiger Schöenherr, 1817 (= Polyrhaphis armiger) the valid name of the species. Polyrhaphis spinipennis Laporte, 1840, is excluded of the fauna of Colombia. New records: P. argentina Lane, 1978, for São Paulo state (Brazil); P. batesi Hovore & McCarty, 1998, for Ecuador; P. belti Hovore & McCarty, 1998 for Ecuador and Colombia; P. gracilis Bates, 1862, for French Guiana; and P. turnbowi Hovore & McCarty, 1998, in doubt, for Peru. Key to the species of the genus is added.